Gerakan Filantropi Islam Berbasis Media Sosial dan Implikasinya Terhadap Pemberdayaan Masyarakat di Indonesia - M Makhrus; Encep Saepudin (ITB AAS INDONESIA Surakarta, 2023)
This article examines the social media-based Islamic philanthropy movement in managing donations in Indonesia. This type of research is a field research through a qualitative-descriptive approach with the research objects being Sedekah Rombongan, Sedekah Bergerak, Laskar Sedekah, Sedekah Kreatif Edukatif, and Kitabisa.com. Data collection techniques were carried out by interview, observation, and documentation. The results of this study indicate that social media-based Islamic philanthropic institutions/ communities creatively optimize websites and social media to collect donations in the form of health, social, and educational service programs. The distribution of donations is mostly for charity activities due to the priority scale for the needs of the poor, then followed up with empowerment programs in the form of providing working capital, training, and business assistance. This Islamic philanthropic movement is able to provide additional understanding, change in behavior, and change attitudes toward the poor to be more productive and empowered. To measure the success of the program, namely by providing two indicators, first, donors donate through the provision of funds, and goods, and are actively involved in program implementation. Second, responding to likes, comments, and shares regarding information shared on social media.